Effect of Kawa Gambir (Uncaria gambir Roxb.) Leaves on Serum LDL in Diabetic Model Rats - Siregar, Muhammad Abi Ghoffari; Rita, Rauza Sukma; Reza, Mohamad; Ali, Hirowati; Rofinda, Zelly Dia; Welan, Rahmani (Jurnal Kedokteran Meditek, 2026)
Background: Kawa gambir leaves, dried in a furnace and brewed as tea, are rich in flavonoids, phenolics, steroids, and tannins and have antioxidant, antihyperglycemic, and antidyslipidemic properties. In diabetes, elevated low-density lipoprotein (LDL) is a dyslipidemic abnormality that increases atherogenic risk. However, the effect of Kawa gambir on LDL in diabetic conditions remains unclear. Objective: To evaluate the effect of Kawa gambir leaf administration on LDL in alloxan-induced diabetic rats. Methods: This experimental study used a post-test-only control group design in 36 Wistar rats randomized into six groups: K−, K+, MET, P1, P2, and P3. Diabetes was induced with alloxan in K+, MET, and P1–P3. MET received metformin, whereas P1, P2, and P3 received Kawa gambir infusions at 1, 2, and 4 g/100 mL once daily for 4 weeks. Serum LDL was estimated using the Friedewald formula. Data were analyzed by one-way ANOVA followed by Least Significant Difference post hoc testing. Results: Mean±SD LDL levels (mg/dL) were 37.16±3.03, 59.90±8.91, 41.30±6.74, 40.60±5.75, 38.95±10.15, and 40.33±7.01 in K−, K+, MET, P1, P2, and P3, respectively. Group differences were significant (p=0.001). The largest numerical reduction versus K+ was found in P2, with a difference of 20.95 mg/dL (95% CI 8.64–33.26). Conclusion: Kawa gambir infusion significantly reduced LDL compared with the untreated diabetic control. Although the 2 g/100 mL group showed the lowest LDL numerically, no significant differences were observed among active treatment groups. These findings support Kawa gambir as an antidyslipidemic agent in diabetic dyslipidemia.